The Role of the the Civil Service Police Unit in Controlling Street Vendors in Yogyakarta: A Theory of Istislah Perspective - Mariyono; Ahmad Baidowi; Ahmad Asroni; Sumarjoko; Husna Nashihin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study examines the role of the Civil Service Police Unit (Satpol PP) in managing and regulating street vendors in Yogyakarta through the lens of the theory of istislah (public interest). The dynamic between efforts to maintain urban order and the protection of small-scale economic rights highlights the complexity of enforcement policies. The theory of istislah serves as a normative foundation to evaluate the extent to which these policies reflect principles of public welfare. The findings reveal that the current enforcement approach, which tends to be repressive, needs to be transformed into a more persuasive and participatory model. More human regulations and the active involvement of street vendors in the policymaking process are essential to achieve social justice and sustainable urban space governance. This study recommends a collaborative, welfare-oriented approach as a long-term solution for managing street vendors in Yogyakarta.